ANALYSIS OF TOURISTS AND HALAL TOURISM BRANDS: A BRAND EQUITY MODEL - Syarif, Ahmad; Farizi, Maulana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The growing trend of Muslims travelling globally has generated opportunities in the halal tourism sector, encompassing travel undertaken for leisure or business purposes beyond traditional tourism contexts. Tourism has emerged as a prominent sector capable of enhancing a nation's economy within a sustainable framework. Expanding the tourist sector will enhance government revenues by augmenting tax income from tourism activities. The global proliferation of the Halal Lifestyle has led to the emergence of Halal Tourism in predominantly Muslim countries, including Indonesia. Halal tourist sites typically develop tourism brands to enhance tourist interest and engagement in visitation. This research examines the impact of engagement on the halal tourism brand. This research is quantitative. The data collection method was a questionnaire administered to 105 tourist respondents. The factors in this study are engagement, brand awareness, brand quality, brand image, and brand loyalty. The research findings indicate that involvement significantly affects brand awareness, image, and quality. The substantial impact of involvement on brand loyalty is mediated by brand awareness, image, and quality.